Analysis of Junior High School Students' Mathematical Disposition Through Congklak Games in Working on Story Problems - Hoiriyah, Hoiriyah; Anas, Aswar; Sulisawati, Dwi Noviani (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
This study is important because of the many challenges faced by students in understanding word problems, especially those related to the concepts of LCM and GCF. Therefore, this study intends to examine students' mathematical disposition in solving word problems related to the concepts of Least Common Multiple (LCM) and Greatest Common Divisor (GCF). The research method used was a qualitative one, analyzing subjects in junior high school. This study was conducted in grade VII of junior high school MHI Bangsalsari. The instruments used include observation, problem study (questions), interviews, and documentation. We analyze the data using qualitative descriptions to solve word problems, utilizing Congklak as an educational tool. The research findings show that the congklak game serves as an excellent medium to increase students' interest in mathematics during the learning process. The implications of this research can help teachers in explaining topics by providing learning media that facilitate student understanding.